Precarization of the youth’s employment in the context of COVID-19 pandemic consequences - E. V. Maslyukova; D. I. Mokrousova; M. A. Pokusaenko (Russian Journal of Economics and Law, 2021)
Objective: to assess the impact of coronavirus (COVID-19) on the youth labor market in the context of the spread of precarization processes in employment.Methods: qualitative methods were used to analyze labor market institutions, together with in-depth interviews and interpretative analysis of actors’ discourses.Results: the COVID-2019 pandemic posed new challenges to the economy and contributed to the active development of new employment formats and employer-employee interaction in the form of informal employment, freelance platforms, and precariat development. The article considers the features and risks of informal and non-standard employment. Based on the labor market analysis, we determined the impact of the pandemic on working conditions, inequality growth and the increasing role of the informal sector. The impact of the crisis on employment conditions for young people with higher education is particularly emphasized. To form the models of students’ behavior under the conditions of labor market instability, the authors conducted in-depth interviews with students and graduates of the Southern Federal University to assess the employment opportunities of university graduates. The characteristics of respondents’ perception of the processes associated with precarization in the context of the COVID-19 pandemic consequences are clarified and specified. Scientific novelty: it consists in the development of theoretical and methodological approaches to the analysis of precarization of youth employment in the context of the COVID-19 pandemic consequences. It is shown that the observed increase of employment precarization is associated with behavioral features caused by dominant behavioral models and distortions in the perception of unstable employment by university graduates in relation to the structural opportunities provided by the labor market.Practical significance: the identified features of employment of the Russian university graduates can be used to develop recommendations for improving the system for monitoring the employment precarization level in the regional labor markets.